Auxiliar de ingeniería, en los procesos constructivos y administrativos celebrados por la alcaldía del Municipio de Mongua Boyacá (2022)
This degree work adheres to the guidelines of a project with an internship modality, where through the activities carried out in a work environment, it seeks to integrate the knowledge learned over 10 academic semesters to the entity where my services will be provided as support. It was possible to consolidate an agreement with the main public entity of the municipality of Mongua, (Municipal Administration of Mongua, Boyacá) planning unit in charge of engineer Orlando Simón Silva, who in where i joined the the first instance appointed me a series of activities where the following stand out: Analysis of legal requirements for the issuance of construction licenses in its different modalities, development of file processes and document management to contracting processes for minimum amount, less amount, provision of services, and abbreviated selection, in addition to being aware of all public works and projects and private that the tutor of the internship sees fit to intervene, as intervening or supervisory orga nisms. It is important to clarify that during the course of the internship other tasks will also other tasks will be required of me depending on their intensity them or not to the project directly. The purpose of this p , they will be evaluated to integrate roject will be to fully and efficiently comply with the activities required by the Engineer or internal work professionals by the planning secretary.